Achieving Immanent Organizational Ethics: Managing Paradoxical Tensions in Packaging - Chen, Sitong Michelle; Bathurst, Ralph J (Wiley, 2026)
Firms face strategic tensions in packaging materials through their conflicting but complementary social, environmental and economic goals in achieving sustainability. Reducing and repurposing plastics, glass, paper and cardboard in agriculture, horticulture and aquaculture is proving a challenge. However, simply eliminating any of these materials does not address strategic tensions. Moreover, the connection between paradox theory and immanent ethics is a nascent research area. Based on the qualitative analysis of data collection from six multiple cases and secondary data, our findings show that New Zealand's primary food firms face multiple strategic tensions in their packaging. We argue that this experience can be regarded as detecting dilemmas and experimenting with new forms of thinking from paradoxical perspectives in immanent ethics. We further contribute to business ethics research by suggesting how paradox theory can be used to better formulate an affirmative approach of immanent organizational ethics through ‘problematizing’, ‘hyper‐attentiveness’ and ‘transformation’. We also established a framework to guide practitioners on how to form such an approach in the business world.
Keywords: 0502 Environmental Science and Management; 1501 Accounting, Auditing and Accountability; 1503 Business and Management; Business & Management; 3501 Accounting, auditing and accountability; 3502 Banking, finance and investment; 3507 Strategy, management and organisational behaviour